ESTUDO DA FORMAÇÃO E RUPTURA DE AGREGADOS: I. SÉRIE LUIZ DE QUEIROZ - Freire, O.; Ranzani, G.; Reichardt, K.; Camargo, O. A. (REVISTA DE AGRICULTURA, 2016)
ESTUDO DA FORMAÇÃO E RUPTURA DE AGREGADOS: I. SÉRIE LUIZ DE QUEIROZ